We can factorize the quadratic as
![x^2 + 3x + 2 = (x - \alpha) (x - \beta)](https://img.qammunity.org/2023/formulas/mathematics/high-school/p5459e1kpjk1qxqznme6blqzxhmrjwodml.png)
and expanding the right side leads to
![x^2 + 3x + 2 = x^2 - (\alpha + \beta) x + \alpha \beta \implies \begin{cases} \alpha + \beta = -3 \\ \alpha \beta = 2 \end{cases}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1x3fkp8pkqoegumhvl618lz5pucp8rvmmt.png)
The polynomial we want will have the factorization and expanded form
![\left(x - \left(1 + \frac\beta\alpha\right)\right) \left(x - \left(1 + \frac\alpha\beta\right)\right) = x^2 - \left(2 + \frac\beta\alpha + \frac\alpha\beta\right) x + \left(1 + \frac\beta\alpha\right) \left(1 + \frac\alpha\beta\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/zxek4vny852b8lwj50uc09ghp8ydjc3ljy.png)
and notice that the constant term is actually the same as (but has the opposite sign of) the coefficient of the
term :
![\left(1 + \frac\beta\alpha\right) \left(1 + \frac\alpha\beta\right) = 1 + \frac\beta\alpha + \frac\alpha\beta + 1 = 2 + \frac\beta\alpha + \frac\alpha\beta](https://img.qammunity.org/2023/formulas/mathematics/high-school/ui1josynuh12truzhn28mkqi13uxj2yepn.png)
Rewrite the coefficient as
![2 + \frac\beta\alpha + \frac\alpha\beta = 2 + (\alpha^2 + \beta^2)/(\alpha\beta) = 2 + \frac{\alpha^2 + \beta^2}2](https://img.qammunity.org/2023/formulas/mathematics/high-school/cwhrce4vz1if1jjbgwyy40nx61bgnqw5tt.png)
Now, observe that
![(\alpha + \beta)^2 = \alpha^2 + 2\alpha\beta + \beta^2 \implies \alpha^2 + \beta^2 = (-3)^2 - 2^2 = 5](https://img.qammunity.org/2023/formulas/mathematics/high-school/k5niaufe6qxl38pdb28nb672a5bp3q2zva.png)
Then the coefficient is simply
, so the polynomial we want is
![\boxed{x^2 - \frac92 x + \frac92}](https://img.qammunity.org/2023/formulas/mathematics/high-school/if6n42g6rlxl3xsxz857exm0uu19kf3cuc.png)